Implementation lessons for school food policies and marketing restrictions in the Philippines: a qualitative policy analysis - Erica Reeve; Anne Marie Thow; Colin Bell; Katrin Engelhardt; Ella Cecilia Gamolo-Naliponguit; John Juliard Go; Gary Sacks (BMC, 2018)
Abstract Background The school environment can enhance children's skills, knowledge and behaviours in relation to healthy eating. However, in many countries, unhealthy foods are commonly available in schools, and children can be exposed to aggressive marketing by the food industry. Taking the perspective of policymakers, this study aimed to identify barriers and enablers to effective school food policy development and implementation in the Philippines. Methods In May 2016, semi-structured interviews were conducted with 21 policymakers and stakeholders involved in school food policymaking and implementation in the Philippines. The Health Policy Analysis Triangle was used to identify interview questions and to guide the thematic analysis. These included the political and socio-environmental context, strengths and limitations of existing policy content, roles and behaviours of actors, implementation processes, policy outcomes, and opportunities to improve policy coherence. Results The Department of Education's policy 'Orders' represented a relatively strong policy framework for the education sector of the Philippines. However, a lack of human and financial resources for implementation, planning, and policy enforcement limited the impact of the policy on the healthiness of school food provision. Ambiguity in policy wording allowed a wide interpretation of the foods eligible to be provided in schools, and led to difficulties in effective monitoring and enforcement. Food companies used existing relationships with schools to promote their brands and compromise the establishment of a stronger food policy agenda. We found a motivated group of actors engaging in policy-oriented learning and advocating for a stronger policy alternative so as to improve the school food environment. Conclusions The adoption of policy mechanisms being used to promote healthy dietary practices in the school setting will be strengthened by more robust implementation planning processes, and resources to support implementation and enforcement. Policymakers should ensure policy language clearly and unequivocally promotes healthier food and beverage options. Steps should be taken to achieve policy coherence by ensuring the objectives of one agency or institution are not undermining that of any others. Where there is reliance on the private sector for school resources, safeguards should be established to protect against conflicts of interest.